(untitled) (Research, Society and Development, 2020)
This study aims to assess the impact of oral health conditions on quality of life and associated factors in 12-year-old. This is a cross-sectional study, with a probabilistic sample of 102 children, in which the HRQOL was assessed using the Child Perceptions Questionnaire (CPQ11-14) in short version (Impact Short Form: 16 -ISF: 16), evaluating , 04 domains, such as functional limitation (DFL), oral symptoms (DOS), social well-being (DSWB) and emotional well-being (DEWB), and sociodemographic characteristics, preventive and clinical aspects in oral health were also evaluated . The average score of CPQ11-14 for the sample was 25 and the demographic and preventive variables in oral health were not shown to be statistically significant in relation to the average score of CPQ11-14. Among the subjective variables, pain of dental origin was associated with the average score of CPQ11-14, as well as with the DFL domain. The need for self-reported dental treatment was shown to be associated with the DOS and DFL of CPQ11-14. Among the normative conditions, only malocclusions were associated with the DEWB of CPQ11-14. Normative conditions had little influence on HRQOL, on the other hand, subjective conditions proved to be strong predictors in relation to the impact of oral health conditions on the quality of life of the children evaluated.